Contrasting patterns of 5S rDNA repeats in European and Asian ecotypes of greater duckweed, Spirodela polyrhiza (Lemnaceae) - Chen, Guimin; Stepanenko, Anton; Borisjuk, Nikolai (Frontiers in Plant Science, 2024)
Ribosomal DNA (rDNA) contains highly conserved, specifically organized sequences encoding ribosomal RNAs (rRNAs) separated by variable non-transcribed intergenic spacers (NTSs) and is abundant in eukaryotic genomes. These characteristics make the rDNA an informative molecular target to study genome organization, molecular evolution, and phylogenetics. In this study, we characterized the 5S rDNA repeats in the greater duckweed Spiroldela polyrhiza, a species known for its small size, rapid growth, highly conserved genome organization, and low mutation rate. Sequence analysis of at least 12 individually cloned PCR fragments containing the 5S rDNA units for each of six ecotypes that originated from Europe (Ukraine) and Asia (China) revealed two distinct types of 5S rDNA repeats containing NTSs of different lengths and nucleotide compositions. The shorter 5S rDNA repeat units had a highly homogeneous 400-bp NTS, with few ecotype-or region-specific single-nucleotide polymorphisms (SNPs). The longer 5S rDNA units had NTSs of 1056-1084 bp with characteristic intra-and intergenomic variants due to specific SNPs and insertions/deletions of 4-15-bp DNA elements. We also detected significant variability in the ratio of short/long 5S rDNA variants between ecotypes of S. polyrhiza. The contrasting dynamics of the two types of 5S rDNA units, combined with the unusually low repeat copy number (for plants) in S. polyrhiza (46-220 copies per genome), shows that this species could serve as an excellent model for examining the mechanisms of concerted evolution and functional significance of rDNA variability.